Adherence to isoniazide prevention therapy in HIV positive patients at Rethabile Community Health Centre Polokwane, Limpopo Province, South Africa - Khan, Mohammad Ishtiaq Hassan (My University, 2017)
Objectives: To assess adherence to Isoniazide Prevention Therapy (IPT) among HIV positive patients in Rethabile Community Health Centre in the Capricorn District of the Limpopo Province. Methods: A cross-sectional study with qualitative and quantitative data collection methods was conducted among HIV positive patients in Rethabile Community Health Centre from January 2013 to December 2013. Consecutive sampling was used to select 90 participants. Adherence was assessed using patient self-rated adherence to IPT, and confirmed by urine tests for isoniazid metabolites. Data was collected using an interviewer administered questionnaire. Information was also obtained from health care works regarding the perception about reason for non- adherence to IPT. Data was analysed using STATA software and thematic analysis. Results: Self-rated adherence to IPT among the participant was 80% where as urine test was positive for Isoniazid metabolites in 73%. While 84% of participants reported that transportation was the main reason for non adherence, 70% also reported distance from the health care as their main reasons for non-adherence to IPT. However, health care providers reported that many patients do not adhere to treatment due to: Lack of money for transport, missed clinic appointment due to rain and fear of losing jobs, use of traditional medicine, wrong belief about IPT, medicine side effects and alcohol consumption. Conclusion: Self – rate adherence to IPT was suboptimal and appears over – estimated among study participants. Interventions to improve adherence to IPT must ensure easy access to healthcare facilities, address wrong perceptions and promote healthy social behaviours
Thesis (M.Med. (Family Medicine)) -- University of Limpopo, 2017
Keywords: Isoniazide adherence; Prevention therapky; HIV positive patients; Rethabile Community Health Centre; Polokwane; AIDS (Disease) - Patients; HIV infections -- Prevention